2019
DOI: 10.17818/nm/2019/2.1
|View full text |Cite
|
Sign up to set email alerts
|

Electrolites and Heavy Metals in Coelomic Fluid of Sea Urchin, Arbacia lixula from Adriatic Sea: Biochemical Approach to Ecotoxicological Study

Abstract: The main circulatory medium of echinoderms is the coelomic fluid. Biochemistry of coelomic fluid is very complex and slightly different from seawater. The main aim of this research was to analyse concentration of electrolytes (potassium, calcium, magnesium, chlorine and sodium), heavy metals (lead, chromium, cadmium and cobalt) and iron in coelomic fluid of sea urchin, Arbacia lixula as an indirect indicator of seawater contamination. After precise statistical evaluation it was observed that electrolyte concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The observed agglomeration of PS NPs in sea urchin CF can be thus ascribed to osmolarity and ion composition of the CF, which is in balance with the surrounding seawater, since sea urchins are considered osmoconformers, although some sea urchin species can sustain positive gradients for the most relevant ions (Mg 2+ , Ca 2+ , and K + ) in case of reduced salinity (Freire et al, 2011;Santos et al, 2013). Moreover, sea urchin CF contains a wide array of biomolecules, produced by the circulating coelomocytes and having key immune functions (Dheilly et al, 2013;Grassi et al, 2019), which are able to adhere on PS NP surface (protein-corona) (Freire et al, 2011;Marques-Santos et al, 2018;Fočak et al, 2019). Our previous findings showed that a highly abundant protein in sea urchin CF, the TPP, tightly bound onto PS NPs surface (hard corona) and provided a new colloidal behavior to PS NPs regardless of their surface charges.…”
Section: The Composition Of Cf Drives Ps Np Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…The observed agglomeration of PS NPs in sea urchin CF can be thus ascribed to osmolarity and ion composition of the CF, which is in balance with the surrounding seawater, since sea urchins are considered osmoconformers, although some sea urchin species can sustain positive gradients for the most relevant ions (Mg 2+ , Ca 2+ , and K + ) in case of reduced salinity (Freire et al, 2011;Santos et al, 2013). Moreover, sea urchin CF contains a wide array of biomolecules, produced by the circulating coelomocytes and having key immune functions (Dheilly et al, 2013;Grassi et al, 2019), which are able to adhere on PS NP surface (protein-corona) (Freire et al, 2011;Marques-Santos et al, 2018;Fočak et al, 2019). Our previous findings showed that a highly abundant protein in sea urchin CF, the TPP, tightly bound onto PS NPs surface (hard corona) and provided a new colloidal behavior to PS NPs regardless of their surface charges.…”
Section: The Composition Of Cf Drives Ps Np Behaviormentioning
confidence: 99%
“…While ion composition of sea urchin perivisceral CF can slightly differ from that of external seawater (Freire et al, 2011;Santos et al, 2013), biomolecules secreted by the circulating coelomocytes and microbes inhabiting the fluid, undergo geographical and seasonal fluctuations also as a consequence of their role in several physiological functions including immune defense (Matranga et al, 2005;Branco et al, 2014). Changes in selected ion composition (Na + , other cations and Cl − ) have been already documented in sea urchin CF as an adaptive strategy of intertidal species to counteract variations toward external environmental conditions, such as for instance environmental changes in seawater osmolarity (Freire et al, 2011;Fočak et al, 2019). Moreover, a significant increase in the concentration of specific proteins of sea urchin CF (i.e., the toposome, also known as major yolk protein and other molecules) has been reported during the reproductive cycle both in female and male specimens (Ura et al, 2017).…”
Section: The Composition Of Cf Drives Ps Np Behaviormentioning
confidence: 99%